Mengenal Gaya Gravitasi: Mekanisme Dibalik Tertariknya Benda-Benda ke Bumi - Lestari, Vika Widiana; Widyorini, Septy; Ridwan, Zalfa Labibah; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Natural Sciences (IPA) play an important role in the development of technology used to support people's lives regarding the application of environmental care concepts and so on. In science, one of the materials studied is the science of style. In science, force is often defined as push or pull, when you pull or push something against an object, it means you are applying force to that object. This article aims to discuss in more depth the mechanism behind the attraction of objects to the earth, one of the effects of which is the result of the earth's gravitational force. The research method used in compiling this article is a qualitative method with data collection and analysis techniques carried out by searching for literature studies through several books and scientific articles as well as other trusted sources. The conclusion is that the attraction of objects to the earth is caused by the force acting on an object, namely the force of gravity. Gravitational force is an attractive force between two objects that have mass. The earth has a very large mass, so objects around it are attracted towards the earth. This is what makes us and everything on the surface of the earth survive. The force of gravity holds the world tightly together, providing the foundation for life and the natural phenomena we experience every day.Â